Artificial Intelligence and Its Role in Enhancing the Efficiency of Compulsory Enforcement of Judicial Decisions: A Comparative Analytical Study - Jana Khaled Al-harbi,; Alhanouf Abdulaziz Alsulami, (International Journal of Law Research and Studies, 2025)
This study examines the impact of artificial intelligence technologies on enhancing the efficiency of compulsory enforcement procedures of judicial rulings in the Kingdom of Saudi Arabia, in light of comparative international experiences. The research problem is represented by the question of the extent to which AI technologies can be utilized to accelerate enforcement procedures and improve their accuracy, while preserving legal safeguards and the rights of the parties, given the current reliance on electronic platforms that still depend largely on human intervention. The study adopts the analytical and comparative methodology by analyzing the Saudi enforcement system and presenting the experiences of the United States of America, the People’s Republic of China, and the United Arab Emirates. The study aims to demonstrate the effect of employing AI in reducing procedural delays, enhancing the efficiency of enforcement judges, and improving mechanisms for identifying and tracking the debtor’s assets with greater accuracy and speed.The study has reached several key findings, most notably that integrating AI technologies into enforcement procedures significantly reduces procedural delays, improves the performance of enforcement judges, and enhances the identification and tracing of debtors’ assets.The study also recommends establishing a comprehensive regulatory framework for the use of AI in judicial enforcement, reinforcing human oversight over the outputs of intelligent systems, and adhering to AI ethics in order to achieve a balance between procedural efficiency, justice, and the protection of the parties’ legal rights.
Keywords: Compulsory Enforcement; Artificial Intelligence; Judicial Decisions; Procedural Efficiency; Enforcement Judge